The use of VA Disability Compensation and Social Security Disability Insurance among working-aged veterans. Issue 3 (July 2015) - Wilmoth, Janet M.; London, Andrew S.; Heflin, Colleen M.
Abstract: Background: Although there is substantial disability among veterans, relatively little is known about working-aged veterans' uptake of Department of Veterans Affairs (VA) Disability Compensation and Social Security Disability Insurance (DI). Objectives: This study identifies levels of veteran participation in VA disability and/or DI benefit programs, examines transitions into and out of VA and DI programs among veterans, and estimates the size and composition of the veteran population receiving VA and/or DI benefits over time. Methods: Data from the 1992, 1993, 1996, 2001, 2004, and 2008 Survey of Income and Program Participation (SIPP) are used to describe VA and DI program participation among veterans under the age of 65. Results: The majority of working-aged veterans do not receive VA or DI benefits and joint participation is low, but use of these programs has increased over time. A higher percentage of veterans receive VA compensation, which ranges from 4.9% in 1992 to 13.2% in 2008, than DI compensation, which ranges from 2.9% in 1992 to 6.7% in 2008. The rate of joint participation ranges from less than 1% in 1992 to 3.6% in 2008. Veterans experience few transitions between VA and DI programs during the 36–48 months they are observed. The number of veterans receiving benefits from VA and/or DI nearly doubled between 1992 and 2008. There have been substantial shifts in the composition of veterans using these programs, as cohorts who served prior to 1964 are replaced by those who served after 1964. Conclusions: The findings suggest potential gaps in veterans' access to disability programs that might be addressed through improved coordination of VA and DI benefits.